(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Stress is defined by the World Health Organization (WHO) as the physical, mental, or emotional response of the human body to external stressors. Many ages, professions, and genders encounter this situation, even in medical environment, where treat and take care of the patients. According to the American Labor Association, nursing is at the top in the list of careers with a high risk of stress. With so many beds, inpatients and outpatients at Thong Nhat General Hospital, nurses and midwives are unevitably under stress and pressure. Objective: To assess the stress status of nurses and midwives at Thong Nhat Dong Nai General Hospital. Research method: Descriptive cross-sectional study on 228 nurses and midwives working at clinical departments of Thong Nhat Dong Nai General Hospital. Assessment of the stress level of nurses and midwives is by using the DASS 21 assessment scale. Research results: The rate of Stress in nurses and midwives working at Thong Nhat Dong Nai General Hospital in 2023 was 38.6%. Nurses and midwives who were assigned a lot of work, had a large number of patients assigned to take care of each day, and worked outside of office hours, had more stress than that those were not. Nurses and midwives who had poor cooperation with patients and their families had higher stress than nurses and midwives who had good cooperation with patients and their families. Conclusion: The rate of Stress in nurses and midwives working at Thong Nhat Dong Nai General Hospital in 2023 was 38.6%. Relationships to stress in the study included: high workload, high-paced work, number of patients assigned daily care, working outside office hours, cooperation of staff the patient and the patient’s family.